2008
DOI: 10.1016/j.bcmd.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Anemia upregulates lipocalin 2 in the liver and serum

Abstract: Lipocalin 2 (Lcn2), a mammalian protein that is expressed and secreted in various pathologic states, binds siderophores, which are high-affnity iron chelators. Besides its role in limiting iron availability to pathogens in the setting of bacterial infection, Lcn2:siderophore complexes can also deliver iron to cells. In this study, we examined Lcn2 regulation in the liver of mice in situations of increased iron utilization, namely, during anemia. Anemia induced by phlebotomy, iron deprivation, or phenylhydrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Anemia and inflammation are known to induce NGAL. 33,34 In this study, we could not demonstrate any association between serum NGAL levels and CRP. Serum NGAL levels were higher in HD patients compared with healthy controls in our study confirming the previous studies 33 probably due to decreased clearance rather than increased inflammation in HD patients.…”
mentioning
confidence: 52%
“…Anemia and inflammation are known to induce NGAL. 33,34 In this study, we could not demonstrate any association between serum NGAL levels and CRP. Serum NGAL levels were higher in HD patients compared with healthy controls in our study confirming the previous studies 33 probably due to decreased clearance rather than increased inflammation in HD patients.…”
mentioning
confidence: 52%
“…It has been reported that hypoxic stress and acute infraction increase Lcn2 expression in mouse macrophages (Hemdahl et al 2006, Jiang et al 2008). This supports the idea that expression of lipocalin-2 is a response that these cells show against hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin (Hamp) and β-actin mRNA levels were measured by real-time PCR in a Rotor Gene 3000™ Real-Time DNA Detection System (Montreal Biotech, Inc., Kirkland, QC, Canada) with the QuantiTect SYBR Green I PCR kit (Qiagen, Mississauga, ON, Canada), as described [20,21], and expression levels of hepcidin and IL-6 were normalized to the housekeeping gene β-actin. The primers employed were: β-actin-5′-…”
Section: Quantitative Reverse Transcriptase-polymerase Chain Reactionmentioning
confidence: 99%